THE EFFECT OF INTELLECTUAL CAPITAL, INSTITUTIONAL OWNERSHIP AND MANAGERIAL OWNERSHIP ON COMPANY’S PERFORMANCE - Yuanita Roslan; Jumatul Rahma Dilla; Penggiri Santi Suwarno (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this study is to examine the effect of intellectual capital, institutional ownership and managerial ownership on company’s performance. The population of this study are the companies listed in the LQ-45 index company during the period of 2015-2017. The independent variables in this study are intellectual capital with proxies (human capital, process capital), institutional ownership and managerial ownership and the dependent variable is company’s performance. The population in this study are all companies listed into LQ-45 index company. The sampling technique used was purposive sampling which result for 33 companies. The analytical methode used was multiple linear regression. The result of the study showed that human capital has no effect on the company’s performance. While process capital, institutional ownership and managerial ownership have a positive effect on the company’s performance. The suggestion for futher research is add another variable or indicator for futher research.